2016
DOI: 10.1104/pp.16.00282
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Pink-Fruited Tomato Mutant Results in the Identification of a Null Allele of the SlMYB12 Transcription Factor

Abstract: The identification and characterization of new tomato (Solanum lycopersicum) mutants affected in fruit pigmentation and nutritional content can provide valuable insights into the underlying biology, as well as a source of new alleles for breeding programs. To date, all characterized pink-pigmented tomato fruit mutants appear to result from low SlMYB12 transcript levels in the fruit skin. Two new mutant lines displaying a pink fruit phenotype (pf1 and pf2) were characterized in this study. In the pf mutants, Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 65 publications
3
34
0
Order By: Relevance
“…No substantial differences in carotenoids were found between y and SM, except the higher all-trans-neoxanthin levels in y_gf and y_r. Conversely, tocochromanol metabolism was altered in y mutant berries as there was a decrease in tocopherols, mainly affecting y and y_r, confirming previous reports [15,59].…”
Section: Biochemical Changes In Fruits Of Colorless Fruit Epidermis Asupporting
confidence: 89%
“…No substantial differences in carotenoids were found between y and SM, except the higher all-trans-neoxanthin levels in y_gf and y_r. Conversely, tocochromanol metabolism was altered in y mutant berries as there was a decrease in tocopherols, mainly affecting y and y_r, confirming previous reports [15,59].…”
Section: Biochemical Changes In Fruits Of Colorless Fruit Epidermis Asupporting
confidence: 89%
“…By means of qPCRs, we confirmed the expression patterns of CHS1 and CHS2 ( Figure S2A,B ). We additionally found that several genes encoding positive regulators of flavonoid (MYB12; [ 91 , 92 , 93 , 94 ]) or anthocyanin biosynthesis (AN2/MYB75, JAF13/bHLH90; [ 95 ]) were also down-regulated in Tu+Al. The anthocyanin biosynthesis regulatory gene ANT1/MYB113 [ 96 ] was not differentially regulated in response to mite feeding.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of carotenoids was performed as reported previously (Liu et al, 2014). Phenylpropanoid analysis was performed by comparing chromatographic and spectral properties with standards and reference DAD-HRMS spectra as previously reported (Fernandez-Moreno et al, 2016;Iijima et al, 2008;Moco et al, 2006). For each analysis, at least three biological replicates were performed.…”
Section: Nonpolar and Semi-polar Metabolite Analysesmentioning
confidence: 99%